Novel indole-based sigma-2 receptor ligands: synthesis, structure–affinity relationship and antiproliferative activity1. Issue 6 (10th June 2015) - Xie, Fang; Kniess, Torsten; Neuber, Christin; Deuther-Conrad, Winnie; Mamat, Constantin; Lieberman, Brian P.; Liu, Boli; Mach, Robert H.; Brust, Peter; Steinbach, Jörg; Pietzsch, Jens; Jia, Hongmei
<x xml:space="preserve">Abstract</x> Novel sigma-2 ligand 1b induced G1 phase cell cycle arrest in DU145 cells and displayed antiproliferative activity.